The magic of lemon drop pie - Linden, Rachel (Berkley, 2022)
"An uplifting novel about a heartbroken young pie maker who is granted a magical second chance to live the life she didn't choose . . . from the bestselling author of The Enlightenment of Bees. Lolly Blanchard's life only seems to give her lemons. Ten years ago, after her mother's tragic death, she broke up with her first love and abandoned her dream of opening a restaurant in order to keep her family's struggling Seattle diner afloat and care for her younger sister and grieving father. Now, a decade later, she dutifully whips up the diner's famous lemon meringue pies each morning while still pining for all she's lost. As Lolly's thirty-third birthday approaches, her quirky great-aunt gives her a mysterious gift-three lemon drops, each of which allows her to live a single day in a life that might have been hers. What if her mom hadn't passed away? What if she had opened her own restaurant in England? What if she hadn't broken up with the only man she's ever loved? Surprising and empowering, each experience helps Lolly let go of her regrets and realize the key to transforming her life lies not in redoing her past but in having the courage to embrace her present"--